Determination of organic chlorine in water via AlCl derivatization and detection by high-resolution continuum source graphite furnace molecular absorption spectrometry. Issue 33 (21st July 2021) - Abad, Carlos; Mimus, Stefanie; Recknagel, Sebastian; Jakubowski, Norbert; Panne, Ulrich; Becker-Ross, Helmut; Huang, Mao-Dong
Abstract : Fast and simple separation and quantification of organic from inorganic chlorine in water by solid-phase extraction and molecular absorption spectrometry. Abstract : High-resolution continuum source graphite furnace molecular absorption spectrometry (HR-CS-GF-MAS) was employed for determining adsorbable organic chlorine (AOCl) in water. Organic chlorine was indirectly quantified by monitoring the molecular absorption of the transient aluminum monochloride molecule (AlCl) around a wavelength of 261.42 nm in a graphite furnace. An aluminum solution was used as the molecular-forming modifier. A zirconium coated graphite furnace, as well as Sr and Ag solutions were applied as modifiers for a maximal enhancement of the absorption signal. The pyrolysis and vaporization temperatures were 600 °C and 2300 °C, respectively. Non-spectral interferences were observed with F, Br, and I at concentrations higher than 6 mg L −1, 50 mg L −1, and 100 mg L −1, respectively. Calibration curves with NaCl, 4-chlorophenol, and trichlorophenol present the same slope and dynamic range, which indicates the chlorine atom specificity of the method. This method was evaluated and validated using synthetic water samples, following the current standard DIN EN ISO 9562:2004 for the determination of the sum parameter adsorbable organic halides (AOX) for water quality. These samples contain 4-chlorophenol as the chlorinated organic standard in an inorganic chloride matrix. Prior to analysis, organic chlorine was extracted from the inorganic matrix via solid-phase extraction with a recovery rate >95%. There were no statistically significant differences observed between measured and known values and for a t -test a confidence level of 95% was achieved. The limits of detection and characteristic mass were found to be 48 and 22 pg, respectively. The calibration curve was linear in the range 0.1–2.5 ng with a correlation coefficient R 2 = 0.9986.